Future Compound Heat-Flash Drought Events Amplify Socioeconomic Exposure and Human Displacement Risks across East Africa - Belay Sitotaw Goshu; Muhammad Ridwan (Britain International for Academic Research (BIAR-Publisher), 2026)
East Africa faces an escalating climate crisis driven by the amplification of compound heat-flash drought (CHFD) events. This study quantifies future CHFD dynamics, socioeconomic exposure, agricultural impacts, and human displacement risks across East Africa under moderate (SSP2-4.5) and high-emissions (SSP5-8.5) scenarios. Using a weighted multi-model ensemble from CMIP6 projections, we analyze historical (1981–2010) and future (2021–2100) periods, integrating population density data, agricultural statistics, and displacement modeling frameworks. Under SSP5-8.5, moderate CHFD frequency is projected to double, while severe events increase by 60% by 2100. Population exposure increases by up to 60% in southern Tanzania and 40–55% in northeastern Kenya, southern Somalia, and eastern Ethiopia. Compound drought-heatwave exposure is linked to 27% (±4.2%) reductions in harvested area and 35% (±5.1%) reductions in crop production, with maize and sorghum most severely affected (β = −0.47 to −0.53, p < 0.01). Rain-fed systems suffer losses exceeding 30%, while irrigated systems demonstrate resilience with losses below 10%. Climate change, accounting for 57.4–71.2% of exposure changes, is the primary driver, with population growth contributing 18.5–26.8%. Climate change could force 6.9–10.1 million people in East Africa to move internally by 2050. These findings demand urgent emission reductions, as mitigation is the most effective strategy for reducing future risks. Adaptation priorities include climate-resilient crops, irrigation expansion, improved flash drought early warning systems, social protection for vulnerable populations, and migration governance frameworks. Region-specific strategies are essential given East Africa's heterogeneous climate responses.